Urban Form and Productivity in México 1995-2015 - Montejano, Jorge; Caudillo, Camilo; Monkkonen, Paavo; Guerra, Erick; Núñez, Juan M.; Garza, Blanca E.; Ávila, Gerardo; Medina, Sandra (European Journal of Sustainable Development, 2020)
Worldwide, urban policies are encouraging more compact development in cities arguing environmental sustainability and higher economic productivity. However, there is limited evidence for the relationship between urban form and economic productivity outside high-income countries. While we know that workers in larger cities are more productive, existing empirical evidence on the relationship between compactness and productivity is only from high-income countries, with a productive service sector. Given that the economic base of many cities in Mexico consists of land-intensive manufacturing activities, policies promoting urban compactness have potential negative impacts on economic growth by restraining expansion. In this paper we explore the relationship in time between urban form/spatial structure and economic productivity in Mexico, by testing the hypothesis that growing in a compact way is positively associated with labor productivity. That hypothesis is not completely rejected because several measures of urban form are positively correlated with higher levels of productivity, and other measures are negatively correlated. As the principal findings are counterintuitive, they raise questions about what is the accepted knowledge of urban growth. Keywords: Urban Form; urban structure; productivity; manufacturing; México.